ANALYSIS OF THE INDONESIAN GOVERNMENT’S DECISION TO BUY RAFALE DASSAULT AIRCRAFT FROM FRANCE - Ali Mardin, Difajrin Septiawan; Paksi, Arie Kusuma; Azizah, Nur (Universitas Padjadjaran, 2024)
This research aims to explain and analyze Indonesia’s decision to buy the Dassault Rafale fighter aircraft from France in 2022. It is known that Indonesia will retire its old F-5 Tiger fighter aircraft and its outdated technology. Indonesia’s purchase of Dassault Rafale fighter aircraft to increase air defense capabilities, strengthen bilateral cooperation and increase national military capabilities. Several options for Indonesia to choose which fighter aircraft to buy, namely Gripen from Sweden, Eurofighter from Austria, Dassault Rafale from France, and Sukhoi Su-35 from Russia. The theory used in this research is Rational Choice. This study used descriptive qualitative method. In this research, data collection techniques were carried out by collecting data through available literature and library materials, mass media, print media, electronic media, books, journals and related articles, as well as other open sources. The results of this research show that Indonesia’s decision to buy the Dassault Rafale fighter aircraft from France was based on two considerations, namely economic considerations where maintenance costs are low, technology transfer, and the potential to increase the national defense industry, increasing independence in the production and maintenance of military defense equipment and political considerations, namely diplomatic relations, regional security and national strategic interests. This choice reflects efforts to strengthen defense and build close military collaboration with partner countries.